RESEARCH-LED HIGHER EDUCATION AND 'THE BIGGER PICTURE' - ŞERBAN PROCHEŞ; CECILE GERWEL PROCHEŞ (Studia Universitatis Babes-Bolyai, 2015)
ABSTRACT. There is increasing pressure on higher education institutions to be research-driven and consequently populated by individuals whose main strength is research. It has already been established that the skills necessary to make a good researcher are not the same with those that make a good teacher. There are, however, other implications with respect to how teaching content is structured in terms of breadth and depth, and how breadth and depth of knowledge in turn may affect students' knowledge in their field - but also broader world views. The aim of this paper is to examine how conflict may arise from the concurrent pursuit of these goals. This discussion is based within the context of split-brain theory (breadth being a right hemisphere attribute, and depth added primarily by the left hemisphere), and highlights the potential of this theory in enhancing the higher education experience.